ESTIMATION OF SUBCARINAL ANGLE USING MINIMUM INTENSITY PROJECTION IN COMPUTED TOMOGRAPHY - Fernandes, Salome Francia; Pradhan, Abhimanyu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The main objective of the study was to determine the normal subcarinal angle (SCA) in an adult patient, to compare the relationship of SCA with patient gender and age, and to correlate the SCA with body mass index (BMI). Methods: A total of 193 subjects (109 males and 85 females) in the age group of 20â€“60 years scheduled for computed tomography thorax at the Department of Radiodiagnosis and Imaging, Kasturba Hospital, Manipal, were included in the study. Plain images were reconstructed into 1.4 mm reformatted image and processed into minimum intensity projection, and measurement was taken using angle tool. Mean and standard deviation was used to determine normal SCA, and independent t-test was used to compare the relationship of SCA with patient's age and gender. Pearson correlationâ€ was used to correlate SCA with BMI. Results- The mean SCA of the adult patient was 69.75Â±3.38Â°. The mean SCA in female was 69.90Â±4.07Â° and in male was 69.63Â±2.75Â°. In the age group of 20â€“40 years, the mean SCA was 70.38Â±3.85Â°, and in the age group of 41â€“60 years, it was 69.25Â±2.88Â°. Conclusion: There was no relationship between SCA and patient's gender; however, the mean SCA of the age group 20â€“40 was found greater than that of 41â€“60 which was statistically significant. BMI has no significant correlation with SCA.